Global Economic Prospects : Financial Markets Outlook, June 2014 - Ju Kim, Eung; Stocker, Marc (World Bank Group, Washington, DC, 2015)
External financing conditions for developing countries have been remarkably favorable in recent months, reflecting expectations of a more drawn-out period of monetary policy accommodation in high-income countries and some narrowing of external vulnerabilities. Additional easing by the European Central Bank, combined with prospects of modest growth and stable inflation in the United States ( Goldilocks recovery ), helped pull down bond yields and volatility worldwide. These benign conditions currently provide support to capital inflows and activity across developing countries, but could at the same time increase the risk of greater and potentially more abrupt market adjustments ahead. Despite some reduction of current account deficits in several developing countries, many remain vulnerable to sudden shifts in investors sentiment and capital outflows. Following a brief period of market turmoil at the start of the year, global financing conditions have eased consider-ably from March to June. Bond spreads for developing countries (i.e. yield difference with 10-year U.S. Treasury bonds) have narrowed, bringing down average borrowing costs to their lowest level since the spring of 2013. Stock markets have also recovered rapidly from a significant sell-off in January/February, despite rising geopolitical tensions and evidence of disappointing activity in the first quarter of the year. As presented in the June 2014 edition of Global Economic Prospects, a more favorable global environment is reflected in upward revisions to capital inflow forecasts for developing countries, now projected to remain broad-ly stable as a percentage of GDP in 2014 and 2015, at around 5.6 percent, before declining again in 2016, to 5.1 percent. While baseline forecasts assume an orderly in-crease in long-term interest rates in high-income countries, the risk of more abrupt adjustments from current low levels has recently increased. Escalating geopolitical tensions or financial stress in some developing countries could also potentially trigger a sudden re-pricing of risk. Despite the recent narrowing of current account deficits in some developing countries, many remain vulnerable to a sharp increase in borrowing costs and/or significant currency depreciations, which could put additional strain on corporate and bank balance sheets.